Comparison of topical nanocolloidal silver formulation use with eosin 2% solution in management of hard-to-heal ulcers in patients with pemphigus vulgaris. (2nd November 2020) - Abedini, Robabeh; Mahmoudi, Hamidreza; Kordestani, Soheila; Habib, Farzaneh Nayeb; Abyaneh, Mitra; Rahemi, Homayoun
Abstract : Objective: To examine the effect of a nanocolloidal silver-based gel called SilvoGel (ChitoTech, Iran) versus eosin (prepared by Razi Hospital, Iran) among patients with immunobullous disease. Method: This blind, randomised controlled study was carried out on patients with pemphigus vulgaris who had hard-to-heal ulcers, divided into two equal-sized groups: one treatment group receiving the nanocolloidal silver-based gel and the control group receiving the conventional eosin. Results: A total of 32 patients participated in the study. In both the treatment and control groups, ulcer area, exudate and tissue type improved significantly (p<0.001 for all measures). A significantly higher rate of improvement in ulcer area was observed in the treatment group compared with the control group (p<0.001). Both patient and physician satisfaction were significantly higher in the treatment group compared with the control group (p=0.003 and p=0.01, respectively). Conclusion: The results of this study indicate that use of the nanocolloidal silver-based gel for treating patients with immunobullous disease including pemphigus could potentially increase the rate and quality of wound healing.